Implementasi Desain Pembelajaran Bermain Peran dalam Meningkatkan Hasil Belajar Sejarah Kebudayaan Islam di MTs Badrussalam Surabaya - Nurul Kumalasari (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2020)
This study aims to describe the various strategies carried out in implementing the learning design of Role Play in improving the Learning Outcomes of Islamic Cultural History. This research is a descriptive study using a qualitative approach. This research was conducted at MTS Badrussalam Surabaya, with student subjects. Data collected through observation, interviews, and documentation. The data validity checking technique used is the triangulation technique. The results showed that the role play learning design is one of the learning designs that can be used in the learning process of Islamic Cultural History and can provide an overview of subject matter or thinking that is still abstract into a pleasant understanding, meaning that learning becomes more concrete. Some strategies that must be considered by educators in implementing fun and non-boring learning designs such as educators must be aware of the latest learning designs in teaching and learning, educators must have the ability to increase the success of student learning, educators are able to develop learning designs, manage learners and conduct an evaluation, and learners accept and can apply the role playing learning design.